Microscopic Characteristics and Qualitative Chemical Composition of two Alpinia Roxb. species Collected in North Central Vietnam - Dam Ngoc Anh, Luu; Thi Phuong Thao, Nguyen; Thanh Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Alpinia calcicola Q.B.Nguyen & M.F.Newman and Alpinia kwangsiensis T.L.Wu & S.J.Chen are belonging to the genus Alpinia Roxb., with only limited  studies focusing on essential oils, chemical constituents, and biological activities. However, there are not many studies on microscopic characteristics and qualitative chemical compounds from these two species. This study is provided database on the leaf microscopic characteristics of A. calcicola and A. kwangsiensis . In addition, the qualitative chemical compound results from the powdered materials of two species has recorded the presence of flavonoids, saponins, carotenoids, lipids, and sterols. Keywords: Alpinia calcicola, Alpinia kwangsiensis, Zingiberaceae, microscopic characteristic, qualitative, chemical composition.